Development and evaluation of the General Surgery Objective Structured Assessment of Technical Skill (GOSATS) - Halwani, Y.; Sachdeva, A. K.; Satterthwaite, L.; de Montbrun, S. (British journal of surgery, 2019)
Background Technical skill acquisition is important in surgery specialty training. Despite an emphasis on competency‐based training, few tools are currently available for direct technical skills assessment at the completion of training. The aim of this study was to develop and validate a simulated technical skill examination for graduating (postgraduate year (PGY)5) general surgery trainees. Methods A simulated eight‐station, procedure‐based general surgery technical skills examination was developed. Board‐certified general surgeons blinded to the level of training rated performance of PGY3 and PGY5 trainees by means of validated scoring. Cronbach's α was used to calculate reliability indices, and a conjunctive model to set a pass score with borderline regression methodology. Subkoviak methodology was employed to assess the reliability of the pass–fail decision. The relationship between passing the examination and PGY level was evaluated using χ2 analysis. Results Ten PGY3 and nine PGY5 trainees were included. Interstation reliability was 0·66, and inter‐rater reliability for three stations was 0·92, 0·97 and 0·76. A pass score of 176·8 of 280 (63·1 per cent) was set. The pass rate for PGY5 trainees was 78 per cent (7 of 9), compared with 30 per cent (3 of 10) for PGY3 trainees. Reliability of the pass–fail decision had an agreement coefficient of 0·88. Graduating trainees were significantly more likely to pass the examination than PGY3 trainees (χ2 = 4·34, P = 0·037). Conclusion A summative general surgery technical skills examination was developed with reliability indices within the range needed for high‐stakes assessments. Further evaluation is required before the examination can be used in decisions regarding certification. Antecedentes La adquisición de habilidades técnicas es importante en el entrenamiento especializado en cirugía. A pesar del énfasis en la capacitación basada en competencias, actualmente hay pocas herramientas disponibles para la evaluación directa de habilidades técnicas al finalizar el periodo de formación. El objetivo de este estudio fue desarrollar y validar un examen simulado de habilidades técnicas para postgraduados en formación en cirugía general (5º año postgraduado). Métodos Se desarrolló un examen simulado de habilidades técnicas de procedimientos de ocho estaciones. Cirujanos generales certificados y ciegos respecto al nivel de formación puntuaron la actuación de 10 postgraduados de tercer año (PGY3) y 9 postgraduados de quinto año (PGY5) usando una puntuación validada. Se utilizó el coeficiente alfa de Cochrane para calcular los índices de fiabilidad, y un modelo conjuntivo para establecer la nota de paso del examen mediante un método de regresión borderline. La fiabilidad de la decisión pasar/no pasar el examen se evaluó usando la metodología Subkoviak. La relación entre pasar el examen y el nivel PGY se analizó mediante la prueba de ji al cuadrado. Resultados La fiabilidad entre estaciones fue de 0,66 y la fiabilidad entre evaluadores de 0,92, 0,97 y 0,76. Se estableció una puntuación para pasar el examen de 176,8/280 (63,1%). La tasa de paso del examen para postgraduados PGY5 fue del 78% (7/9) en comparación con el 30% (3/10) para los posgraduados PGY3. La fiabilidad de la decisión pasar/no pasar fue pₒ= 0,88. Los postgraduados PGY5 presentaban una probabilidad significativamente superior de pasar el examen en comparación con los postgraduados PGY3 (χ2 = 4,34, P = 0,037). Conclusión Se desarrolló un examen sumatorio de habilidades técnicas de cirugía general con índices de fiabilidad dentro del rango necesario para este tipo de valoraciones. Se requiere una evaluación adicional antes de que el examen se pueda utilizar en las decisiones de certificación. Competency‐based training and assessment is receiving great attention in surgical education. The aim of this study was to develop and evaluate a general surgery summative assessment tool for senior trainees. With further study and confirmation, performance on this examination could help with decisions on surgical trainee certification. Discriminating technical skills examination